NOx SCR with decane using Ag–MFI catalysts: on the effect of silver content and co-cation presence. Issue 9 (9th December 2015) - Bartolomeu, Rui; Mendes, Acácio Nobre; Fernandes, Auguste; Henriques, Carlos; da Costa, Patrick; Ribeiro, M. Filipa
Abstract : A series of 4 and 9 wt% Ag/MFI catalysts were prepared using MFI zeolites containing different co-cations (H + and Na + ). Abstract : A series of 4 and 9 wt% Ag/MFI catalysts were prepared using MFI zeolites containing different co-cations (H + and Na + ). The effect of the presence of these co-cations, as well as the silver loading, on the stabilisation of different Ag species was assessed by powder XRD, TEM, H2 -TPR, in situ DRS UV-vis and pyridine adsorption followed by FTIR. The results obtained from all techniques allowed the comparison of the catalysts regarding the distribution and nature of the Ag species and their catalytic performance for the selective catalytic reduction (SCR) of NO x, in an excess of oxygen, using n -decane as the reductant. It was observed that with an Ag content of 4 wt%, the presence of Na + does not affect the activity of the catalyst towards N2 formation, whereas with an Ag content of 9 wt%, it decreases N2 formation. This negative effect observed in the deNO x reaction can be attributed to the decrease in the amount of oxidised Ag species (Ag + and Ag n δ + ) and the predominance of Ag 0 particles in the samples containing Na. Furthermore, the absence of exchange-sites in the zeolite structure also led to a complete loss of activity. Hence, the exchange-sites are crucial for the stabilisation of the Ag species ( e.g. Ag + and Ag n δ + ) that are active for the NO x SCR reaction with n -decane.